Analysis of Testing and Measuring the Work Environment against Air Microorganisms in PT. PLN (Persero) UPK Nagan Raya - Muharrasya, Aca Rianda; Akmal, Abdiel Khaleil (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Working environment conditions that do not meet the requirements can cause health problems in workers. Air quality, temperature, radiation, ventilation, lighting, and various chemicals in the building are very important causes of complaints and symptoms of microorganisms. This study aims to determine the air microorganisms in the K3 room of PT. PLN UPK Nagan Raya and analyze the air for microorganisms in the K3, WTP, and environmental rooms. Based on the study's results, the multiple linear regression test (simultaneously) obtained a p-value of 0.656, a p-value value > 0.05. It can be concluded that all independents significantly affect dependent variables. The partial test results showed significant values, namely 0.699 and 0.656, and the test results of the multiple linear regression equations obtained values Y = -1702,500 X1 + 20,650X2.